AWARENESS OF THE IMPORTANCE OF GOOD NUTRITION DURING PREGNANCY AMONG WOMEN OF CHILDBEARING AGE IN DOKA, KACHIA LOCAL GOVERNMENT AREA OF KADUNA STATE - Dakare, Monday A.; Adamson, M.; Muhammad-Idris, Z. K.; Ashafa, H. M. (FUDMA JOURNAL OF SCIENCES, 2025)
Pregnancy requires a proper nutrition schedule as it is of major importance for one’s health and well-being and during a critical time period as child bearing, a woman undergoes major biological, physical, psychological and social transformations that her body has to keep up with. Deficiency of micro and macronutrient predispose the fetus to neural tube defects, preterm birth, and low birth weight for gestational age. This study aims to create awareness on the importance of good nutrition during pregnancy among women of childbearing age in Doka, Kachia Local Government Area, Kaduna, Kaduna State. This study uses a cross-sectional and descriptive design, 80 women of childbearing age were randomly selected from Doka, Kachia Local Government Area, Kaduna, Kaduna State. The collated data was statistically analyzed by using descriptive statistics. The result reveals that most (36.25%) of the respondents were within the age range of 20-24years with a larger (41.25%) percentage of the respondent having secondary education. Educational level and age are risk factors for pregnant women, especially young adults. Most of the selected respondents have some level of awareness on nutrition during pregnancy In conclusion, our conceptualization of nutrition awareness has shown to be fruitful in ascertaining the understanding level of the respondents which can help in contributing to the pregnancy outcome when due.